Converting photographs into colouring pages - Chong, Jia Yan (2019)
Colouring is an extremely therapeutic activity, and there are many positive benefits associated with it. Colouring applications, albeit available in the market, are not entirely free. In order to use certain functions in these applications, one of which is to upload one’s own photo to colour, users are required to pay to have access to such functions. Hence, this project aims to develop a program that transform coloured photographs into colouring pages, so that users can use it for free and do not have to pay to customize their colouring pages. The program is designed and created using the MATLAB software and the Image Processing Toolbox that MATLAB provides. The main function of the program is to colour images that are chosen and uploaded by the user. The user can choose to have their chosen image converted to a black and white image or a grayscale image. The project also allows users to undo and redo their action, and when they are done, they can save their final product in their computer. The resultant program is satisfactory in terms of functionality and has met the project goals. However, the program could be further enhanced and improved on to provide more image processing functions that enables users to do more things within the program.